The constitution of São Paulo urban space (Brazil). Aspects about the indian question in the contradictory relation between city and rural space - Alfredo, Anselmo (GEOUSP Espaço e Tempo (Online), 2003)
We dial in this article with de aprehension of how, inspite of São Paulo city has only been constituted as such in the last decades of nineteenth century, the meanings that the urbanization of São Paulo will realize was already pressuposted in the agrarian espacialities of colonial period. We aim to present how, inspite of the urban center, or even, the different clusters arround of São Paulo has been defined through the rhythms of agrarian life, it already had a relation (rural/urban) wich result would express in the realization of Real property in the very interior of the city. This relation, it proposes itself as a rationalization of the rural space where the city were the necessary contradictory element for such, indeed, the diverses clusters were based in a social organization that were known as "aldeamentos", a subordination of the indian villages accord the necessity of the Portuguese metropolis: maintence of the indians as eslaves, so that would be possible to use their work force in differents services for the Crown s interests. We try to develop, however, how the agrarian space itself, in the specific case of this research, was the produccion of a colonial strategy but that will conform the constitution of a centrality that would dominate it: the urban space fundamented by the private property